Modulation of the human sensorimotor system by afferent somatosensory input: evidence from experimental pressure stimulation and physiotherapy - Pavel Hok (Biomedical Papers, 2020)
Peripheral afferent input is critical for human motor control and motor learning. Both skin and deep muscle mechanoreceptors can affect motor behaviour when stimulated. Whereas some modalities such as vibration have been employed for decades to alter cutaneous and proprioceptive input, both experimentally and therapeutically, the central effects of mechanical pressure stimulation have been studied less frequently. This discrepancy is especially striking when considering the limited knowledge of the neurobiological principles of frequently used physiotherapeutic techniques that utilise peripheral stimulation, such as reflex locomotion therapy. Our review of the available literature pertaining to pressure stimulation focused on transcranial magnetic stimulation (TMS) and neuroimaging studies, including both experimental studies in healthy subjects and clinical trials. Our search revealed a limited number of neuroimaging papers related to peripheral pressure stimulation and no evidence of effects on cortical excitability. In general, the majority of imaging studies agreed on the significant involvement of cortical motor areas during the processing of pressure stimulation. Recent data also point to the specific role of subcortical structures, such as putamen or brainstem reticular formation. A thorough comparison of the published results often demonstrated, however, major inconsistencies which are thought to be due to variable stimulation protocols and statistical power. In conclusion, localised peripheral sustained pressure is a potent stimulus inducing changes in cortical activation within sensory and motor areas. Despite historical evidence for modulation of motor behaviour, no direct link can be established based on available fMRI and electrophysiological data. We highlight the limited amount of research devoted to this stimulus modality, emphasise current knowledge gaps, present recent developments in the field and accentuate evidence awaiting replication or confirmation in future neuroimaging and electrophysiological studies.